A proposal for a new soccer-specific stadium for the Louisville City FC soccer team - Hambrick, Marion E. (SAGE Knowledge. Cases., 2018)
Louisville City FC (football club), a professional soccer team located in Louisville, Kentucky, received a mandate from the United Soccer League: build a soccer-specific stadium by 2020 to remain in the league. At the time of this announcement, the team played its home games at Louisville Slugger Field, a professional baseball stadium owned by the city of Louisville and managed by the Louisville Bats, a minor league baseball team. In response, local government officials paid $75,000 for a facility feasibility analysis to review the potential effects of building a soccer-specific stadium. The analysis offered insights into the advantages and disadvantages of constructing a new stadium. Louisville FC leaders and local government officials weighed the various options provided in this report, including three proposed stadium plans ranging from $30 million to $50 million. The team would like to use this information and move forward with construction. Stadium opponents, however, cite the financial difficulties with another local sports facility, the KFC Yum! Center, and question whether building a new stadium represents a sound decision. This case study gives readers an opportunity to evaluate the merits of the stadium proposal and whether the team and city officials should pursue this decision.